Female labor force participation and economic growth– Re-examination of u-shaped curve - Ewa Lechman (Gdańsk University of Technology, Faculty of Management and Economics, 2014)
The paper contributes by providing new insights into the relationship between female labor force and economic growth in 162 countries over the period 1990-2012. We anticipate uncovering U-shaped impact of economic growth on female labor force. To examine the previous we deploy longitudinal data analysis assuming non-linearity between variables. Our main findings support the hypothesis on U-shaped relationship between female labor force participation and economic growth, however high cross-country variability on the field is evident.
Keywords: J21; O10; O50; 330; female labor force; women; economic growth; U-shaped curve; panel data